1998
DOI: 10.1097/00000539-199807000-00038
|View full text |Cite
|
Sign up to set email alerts
|

Visual Evaluation of Residual Curarization in Anesthetized Patients Using One Hundred-Hertz, Five-Second Tetanic Stimulation at the Adductor Pollicis Muscle

Abstract: After the administration of muscle relaxants, the absence of visual fading at the adductor pollicis, elicited in anesthetized patients by 100-Hz, 5-s tetanus, is compatible with a train-of four ratio > 0.85. Therefore, clinical observation of fading after 100-Hz, 5-s tetanus seems to be a highly sensitive test in evaluating residual paralysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…An important question regarding any in vitro study such as the present one, is whether the findings can be extrapolated to the in vivo situation and ideally to the clinical set-ting. In this regard, the effective plasma concentrations attained by atracurium in patients, calculated from its usual range of doses (0.3 to 0.6 mg/kg, Payne & Hughes 1981;Baurain et al 1998), volume of distribution (0.16 l/kg, Ward et al 1983) and molecular weight (1243.4, Stenlake et al 1983) is in the range of 1.5 to 3.0 mM. This overlaps the range of concentrations used in our experimental conditions in vitro.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…An important question regarding any in vitro study such as the present one, is whether the findings can be extrapolated to the in vivo situation and ideally to the clinical set-ting. In this regard, the effective plasma concentrations attained by atracurium in patients, calculated from its usual range of doses (0.3 to 0.6 mg/kg, Payne & Hughes 1981;Baurain et al 1998), volume of distribution (0.16 l/kg, Ward et al 1983) and molecular weight (1243.4, Stenlake et al 1983) is in the range of 1.5 to 3.0 mM. This overlaps the range of concentrations used in our experimental conditions in vitro.…”
Section: Discussionsupporting
confidence: 67%
“…This overlaps the range of concentrations used in our experimental conditions in vitro. So, it is fair to suppose that the mechanisms we disclosed for atracurium in vitro in the present work are also operative in vivo in the clinical setting, where atracurium is known to induce fade of the tetanic contraction (Payne & Hughes 1981;Baurain et al 1998) with similar characteristics to the fade observed in vitro in the present work.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Baurain et al. [12] found a visual absence of fading after a 100 Hz, 5 s tetanic stimulation to be comparable to a TOF ratio of 0.85. However, recent studies of this topic have shown that the sensitivity of using a tetanic stimulation in detecting residual curarisation is about 70% but with a low specifity of only 50% [11].…”
Section: Basic Considerationsmentioning
confidence: 99%
“…Relying on tactile or visual evaluation of fade after a 50 Hz or 100 Hz tetanic stimulation is also unreliable [88–90]. Feeling or observing fade in response to 100 Hz tetanic stimulation probably has the highest sensitivity in diagnosing PORC [90, 91]. However, some patients show fade even without exposure to a NMBA.…”
Section: Postoperative Residual Curarisationmentioning
confidence: 99%